Psoriasis and inflammatory skin diseases 2020 - Gylienė, Iveta; Grigaitienė, Jūratė; Valiukevičienė, Skaidra (Vilnius University Proceedings, 2020)
The aim of this virtual conference is to share and increase dermatovenereology specialists’ knowledge about chronic inflammatory dermatoses. Attendees will be able to listen to latest scientific updates not only on psoriasis, but atopic dermatitis, hidradenitis suppurativa, acne, rosacea and other diseases as well. Experienced lecturers from Lithuania and other countries will present their research works, reviews and rare clinical cases, which are both of theoretical and practical benefit.
Keywords: psoriasis; virtual conference; abstracts; inflammatory; skin diseases; biologic therapy; Lithuania